deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

PlotToSat: A tool for generating time-series signatures from Sentinel-1 and Sentinel-2 at field-based plots for machine learning applications - Milto Miltiadou; Stuart Grieve; Paloma Ruiz-Benito; Julen Astigarraga; Verónica Cruz-Alonso; Julián Tijerín Triviño; Emily R. Lines (Environmental Modelling & Software, 2025)

Marine snow as vectors for microplastic transport: Multiple aggregation cycles account for the settling of buoyant microplastics to deep‐sea sediments - Nan Wu; Stuart W. D. Grieve; Andrew J. Manning; Kate L. Spencer (Limnology and Oceanography, 2025)
Many studies have reported the paradoxical observation of high concentrations of low‐density microplastics (plastic particles μ m in diameter can reach the ocean bottom. This theoretical model refines our ability to predict and understand the global and long‐term fate, transport, and inventory of microplastics in the ocean interior, the influence of microplastics on the biological carbon pump and the efficacy of plastic management policies.

PyShoreVolume 1.0.0: A Python based Shoreline Change and beach Volumetric Change Analysis tool - Owen C. James; Daniel N. Schillereff; Stuart W.D. Grieve; Andreas C.W. Baas (Computers & Geosciences, 2024)

Diffusion MRI as a complementary assessment to cognition, emotion, and motor dysfunction after sports-related concussion: a systematic review and critical appraisal of the literature - Sarah C. Hellewell; Thomas Welton; Alan J. Pearce; Jerome J. Maller; Stuart M. Grieve (Brain Imaging and Behavior, 2021)

Gray Matter Atrophy in the Cerebellum—Evidence of Increased Vulnerability of the Crus and Vermis with Advancing Age - Teresa Yu; Mayuresh S. Korgaonkar; Stuart M. Grieve (The Cerebellum, 2017)

Is the Alzheimer’s disease cortical thickness signature a biological marker for memory? - Edgar Busovaca; Molly E. Zimmerman; Irene B. Meier; Erica Y. Griffith; Stuart M. Grieve; Mayuresh S. Korgaonkar; Leanne M. Williams; Adam M. Brickman (Brain Imaging and Behavior, 2016)

Cardiac magnetic resonance imaging of rapid VCAM-1 up-regulation in myocardial ischemia–reperfusion injury - Stuart M. Grieve; Jacob Lønborg; Jawad Mazhar; Timothy C. Tan; Edwin Ho; Chia-Chi Liu; William Lay; Anthony J. Gill; Philip Kuchel; Ravinay Bhindi; Gemma A. Figtree (European Biophysics Journal, 2013)

Early Life Stress on Brain Structure and Function Across the Lifespan: A Preliminary Study - Donna L. Seckfort; Robert Paul; Stuart M. Grieve; Brian Vandenberg; Richard A. Bryant; Leanne M. Williams; C. Richard Clark; Ronald A. Cohen; Steven Bruce; Evian Gordon (Brain Imaging and Behavior, 2008)